The principles of divine service: An enquiry concerning the true manner of understanding and using the order for morning and evening prayer, and for the administration of the Holy Communion in the English Church - Freeman, Philip (James Parker and Co., 1880)
v. 1. Morning and evening prayer.--v. 2. Holy Communion.